Investigation of a helicopter model rotor wake interacting with a cylindrical sling load - De Gregorio, F.; Visingardi, A.; Nargi, R.E. (My University, 2018)
An experimental and numerical investigation on a four-blade isolated main rotor in hover condition has been carried out in order to investigate the effect of the rotor downwash on a tethered load. A sling load was located at different positions below the rotor disk in order to evaluate the mutual interference between the rotor wake and the immersed body. A radio controlled helicopter model, largely customized and modified for the scope of the experiment, was used as rotor rig. The sling load was reproduced by a low aspect ratio (l/d=2) cylinder being representative of typical loads as oil drums, water containers or engine canisters. Furthermore, the cylinder flow wake is a well known case largely investigated in literature and a good test case for computational fluid dynamics simulation. A six components balance measured the rotor loads calculating the figure of merit. The cylinder pressure distribution together with the flow field characteristics were also measured. Numerical simulation were carried out by using an unsteady, inviscid and incompressible free-wake vortex lattice boundary element methodology solver for multi-body configurations. The paper reports the main rotor wake characteristics up to 3 radii distance from the rotor plane with and without sling load. The effect of the downwash on the cylinder varying the distance and the changes induced by the presence of the cylinder are discussed.